Pembuktian Terbalik Sebagai Upaya Optimalisasi Penanganan Tindak Pidana Korupsi di Indonesia - Hafizah Hasan (Faculty of Law, Universitas Lampung, 2020)
Corruption occurs along with the development of the increasingly common era, which demands law enforcement and the legal justice system in Indonesia to make an effort in optimizing the handling of corruption by focusing on the evidence system. Singapore represents one of the countries that has implemented a reverse proof system. According to the Singapore 2019 Transparency International Corruption Perceptions Index (TI-CPI), the third position with the lowest level of corruption. Therefore Singapore's achievements will help to measure the efforts to optimize the handling and prevention of fraud in Indonesia. Through a literature study that compares the reversal proof system in the country of Singapore by using deductive logic to draw general matters for research results.